Climate change researches in regional responses - Mathews, Daisy (Callisto Reference, 2015)
This book presents a descriptive account on the concepts of climate change and discusses research-focused information regarding its regional responses. Researchers from across the globe have contributed valuable information in this insightful book. This book discusses various topics related to this field like forecasting, measurements as well as observations of meteorogical visibility, grids in numerical weather and climate models, etc. Updated in-depth information has been compiled in this book. The primary aim of this book is to serve as a valuable source of information for researchers, scientists, students, etc. interested in studying about the concepts of climate change and related topics.